Academic Skill Learning and the Problem of Complexity I: Creational Purposeful Integrated Capability at Skill (CPICS) - Martin F. Gardiner (Northeast Journal of Complex Systems, 2019)
Physical and mental skills are intended to achieve success at acting purposefully. As capability at any skill increases, the need to adjust details of application to complexity of context and goals will increase as well. It will become more and more important to prepare mentally for what I now term Creational Purposeful Integrated Capability at Skill (CPICS). This paper develops what I mean by CPICS. Theory concerning Complex Dynamical Systems (CDS) such as the brain and other evidence points to the likelihood that the mental operations by which our brain produces any kind of skillful behavior cannot remain constant, but rather must develop through stages for skill to progress most profitably. Using early stages of math learning as an example, I propose that what can hold back some students at development of a skill is that even if presented with all the information need for progress, some students have not yet discovered how to make the most useful mental restructuring that is also needed. This paper proposes and discusses as an example details of what may be especially useful restructuring for early stages of math skill learning. This example is then taken as helping to identify the more general type of restructuring that is especially useful for addressing complexity of application that produces CPICS at every stage of skill improvement.